ANALISIS ETOS KERJA BERDASARKAN KEPEMIMPINAN DALAM PENYELENGGARAAN PEMERINTAHAN KAMPUNG DAN KINERJA APARATUR - irene ipijei; Maria Natalia W. Epin (Musamus Accounting Journal, 2021)
Human resources are assets in an organization that cannot be replaced by other organizational assets. Human resource assets in the organization are all stakeholder elements in the organization based on their respective roles. Leadership in this current era is required to be able to work more professionally, decisively, and wisely, this is because there are people who have also been able to be critical in responding to the existing environment. The purpose of this research is to look at leadership in influencing work ethic and work performance. The research procedure is a descriptive qualitative research method. This research was conducted in the Jagebob district. The sampling technique was purposive and snowball sampling, with a sample of 9 informants. Data collection techniques are observation, interviews, and documents with data analysis techniques Miles and Huberman model. The result of this study is that current leadership requires skills, policy firmness because it has been balanced by the critical attitude of the community in responding to every phenomenon in the environment. Incompetent, decisive, and wise leadership can reduce the work ethic of members of the organization, affect the work behavior of organizational members, and work discipline. In running the government, the leadership must have good coordination from the district to the district level so that obstacles can be resolved because the development of a region requires the role of all government apparatus. The progress of a government in an area occurs when there are employees who have good work performance without any pressure on organizational management from parties who are considered not direct members of the organization. Keywords: Leadership Style, Work Ethic, Village Government, Work Performance.